Peripartum Cardiomyopathy: Strong Suspicion and Prompt Management Saves the Life of A Mother; A Case Report - Kishore, Ruchi; Lambodari, Pratibha; Agrawal, Anshu; Singh, Neelam (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Peripartum cardiomyopathy is a rare dilated cardiomyopathy of unknown aetiology affecting 1 in 3000 to 4000 livebirths. The overall morbidity and mortality rate are as high as 20%-50%. The clinical presentation mimics pre-eclampsia, pulmonary embolism etc. Hence, it is often misdiagnosed. This case report aims to make health professionals aware about the significance of timely diagnosis and management of this rare entity. Case report: A 29 year old, booked 2nd gravida with twin pregnancy presented at 36 weeks of gestation in active phase of labour to the labour room with 1st twin in vertex presentation. She was given trial of labour. Soon after the delivery of 1st twin she developed acute breathlessness with bilateral diffuse coarse crepitations. Echocardiography suggested peripartum cardiomyopathy. Patient was shifted to ICU and was treated with respiratory support, diuretics, cardiotonic and other supportive measures. The challenge here was the delivery of the 2nd twin which was an IUFD. Vaginal delivery of the 2nd twin was conducted after stabilization of the mother. Prevention of PPH was well taken into account with injection oxytocin. The patient symptomatically improved on 5th postpartum day and was discharged on 7th postpartum day, explaining the need of regular follow up. Conclusion: Acute onset of air hunger in a previously asymptomatic women in labour should always raise a suspicion of peripartum cardiomyopathy. Timely diagnosis and management saves the life of a mother.
Keywords: Peripartum cardiomyopathy; echocardiography; twin